Let c(s) = -s**2 + 13*s. Let y be c(12). Solve -y = -0*k + 3*k for k.

-4

Suppose -5*g - 21 = 4. Let y = -3 - g. Let r = 0 + y. Solve r*q = -0*q for q.

0

Let c be (5 + 1)*(-4)/(-6). Suppose 12 - 48 = -c*y. Solve 0*u - 3*u = y for u.

-3

Suppose -2*u = -3*u. Suppose u = 3*k - 6 - 39. Solve -4*v = -7*v + k for v.

5

Let q = 28 - 27. Solve 0 = t - 3 - q for t.

4

Let k(n) = n3 + 3*n2 + n - 2. Let j be k(-2). Let u = 20 - 12. Let w be 134 - 2/u. Solve -w*i - 12 = -j*i for i.

-4

Let c = -11 - -13. Suppose b = -c*z + 6, 3*b = z + 3*z - 12. Solve -z*f + 2*f + 4 = 0 for f.

4

Suppose 3*x + 2*x = -0*x. Solve -r + x - 2 = 0 for r.

-2

Let c(v) = -v + 4. Let y be c(2). Suppose -y*o = 4 - 16. Solve o*l - 3 = 3*l for l.

1

Let y = 37 - 22. Let a be (-2)/3 + 10/y. Solve a = -2*q - 3*q - 25 for q.

-5